A Real-Time PCR Assay for Detection of Low Pneumocystis jirovecii Levels - Ruiz-Ruiz, Susana; Ponce, Carolina A.; Pesantes, Nicole; Bustamante, Rebeca; Gatti, Gianna; San Martin, Viviana; Gutierrez, Mireya; Bórquez, Pamela; Vargas, Sergio L.; Magne, Fabien; Calderón, Enrique J.; Pérez-Brocal, Vicente; et al. (Frontiers in Microbiology, 2022)
A new real-time PCR assay using SYBR Green was developed for specific detection of low levels of Pneumocystis jirovecii. Two primers set targeting the family of genes that code for the most abundant surface protein of Pneumocystis spp., the major surface glycoproteins (Msg-A), and the mitochondrial large subunit rRNA (mtLSUrRNA) gene, simultaneously detect two regions showing higher sensitivity than other detection methods. All samples identified as positive by the nested-PCR method based on the detection of Pneumocystis mitochondrial large subunit rRNA (mtLSUrRNA), considered as the gold standard diagnostic technique for this pathogen, were also found positive using our new real-time Msg-A/mtLSUrRNA PCR protocol, even three nasal aspirate samples that were negative for both rounds of nested-PCR. Furthermore, we read both rounds of the nested-PCR results for comparison and found that some samples with no PCR amplification, or a very weak band, in the first round correlated with higher Ct values in our real-time Msg-A/mtLSUrRNA PCR. This finding demonstrates the ability of this new single-round protocol to detect shallow Pneumocystis levels. This new assay provides a valuable alternative tool for P. jirovecii detection in individuals, as it is fast and sensitive.